''Everywhere in chains'': Work, commodity chain analysis, and the subversion of accountability. (1st July 2011) - ,
Abstract : ''Chain'' literatures analyse the production and exchange linkages that bind nodes of production into a linear sequence. These chains typically extend beyond the remit of any one jurisdiction, firm, or civil-societal institution. Conventional treatments of accountability are informative, but rarely have chains in mind The concept of an accountability chain addresses these gaps. A central consideration in governance and accountability along a chain is the necessary bias in communications introduced by the very media that make accountability relations possible. This article addresses some basic strategic considerations that arise when accountability relations are viewed this way. It also addresses accountability itself and its worrisome degree of ''modesty'' When the activities that are supposed to be monitored occur too much beyond the direct observation or control of the monitors.